2011
DOI: 10.1590/s1516-35982011000600015
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of lambs fed silk flower hay (Calotropis procera SW) in the diet

Abstract: -The objective of this work was to evaluate the influence of using silk flower hay replacing corn and soybean meal on physical-chemical and sensorial traits of lamb meat. It was used 32 intact Morada Nova male lambs (12.7 ± 2 kg initial body weigth) on feedlot system, distributed in a completely randomized design with four levels (0, 15, 30 and 45% on dry matter basis). The use of silk flower hay in the diet influenced quality of meat and carcass, leg weight, tissue composition, moisture, juiciness and flavor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…Contrarily to what it was observed in the present study, several authors have reported that the inclusion of alternative forage sources in the diets of lambs may influence meat sensory quality (Madruga et al 2005;Costa et al 2011;Moreno et al 2015). Madruga et al (2005) observed differences in the meat from Santa Table 4.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Contrarily to what it was observed in the present study, several authors have reported that the inclusion of alternative forage sources in the diets of lambs may influence meat sensory quality (Madruga et al 2005;Costa et al 2011;Moreno et al 2015). Madruga et al (2005) observed differences in the meat from Santa Table 4.…”
Section: Resultssupporting
confidence: 75%
“…The values found in this study are thus similar to those described in the literature. Costa et al (2011) observed no changes in meat colour using percentages (15, 30, and 45%) of silkflower hay replacing the concentrate in the diet of Morada Nova lambs finished in the feedlot. Similarly, Moreno et al (2015) reported no changes in meat colour when evaluating saltbush hay (Atriplex nummularia) in finishing diets for Santa Ines lambs in the feedlot.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…However, they are within the range found in the literature for this variety. ----------------------------%--------------------------- Similar dry matter results were found by Costa et al (2011). They obtained 30.4% of dry matter also in the fourth punch, whereas Cruz et al (2009) found an average of 30.5%.…”
Section: Chemical-nutritional Analysissupporting
confidence: 82%
“…In NW Brazil [114], and to a smaller extent in parts of India [115], silk flower hay (SHF, C. procera SW.) has been reported to be suitable for feeding goats, sheep, and camels. In sheep and goat farming, it was noted that substitution of corn and soybean by silk flower hay of up to 30% did not decrease the nutrient uptake by Morada Nova lambs [116] and did not decrease the sensory attributes of their meat [117] or important attributes of the milk of the goats [118].…”
Section: Animal Feedmentioning
confidence: 99%